2020
DOI: 10.1002/1878-0261.12635
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as radio‐response biomarkers for breast cancer stem cells

Abstract: In breast cancer (BC), the presence of cancer stem cells (CSCs) has been related to relapse, metastasis, and radioresistance. Radiotherapy (RT) is an extended BC treatment, but is not always effective. CSCs have several mechanisms of radioresistance in place, and some miRNAs are involved in the cellular response to ionizing radiation (IR). Here, we studied how IR affects the expression of miRNAs related to stemness in different molecular BC subtypes. Exposition of BC cells to radiation doses of 2, 4, or 6 Gy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“… 27 Griñán-Lisón et al showed that miR-15b is tightly correlated with radio-resistance, stemness properties, and metastasis in BC, and could be applied as an attractive biomarker in the clinical arena, predominantly in radiotherapy so as to predict and monitor the tumor response to radiation. 28 However, whether miR-15b contributes to acquired endocrine resistance in BC and the potential mechanisms involved, remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Griñán-Lisón et al showed that miR-15b is tightly correlated with radio-resistance, stemness properties, and metastasis in BC, and could be applied as an attractive biomarker in the clinical arena, predominantly in radiotherapy so as to predict and monitor the tumor response to radiation. 28 However, whether miR-15b contributes to acquired endocrine resistance in BC and the potential mechanisms involved, remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…miR-210 is highly radioresistant and overexpressed under hypoxic conditions [ 80 , 94 ]. Lastly, depending on the radiation dose delivered the expression of miRNAs varies in breast cancer and can be used as a biomarker in a personalized treatment [ 95 ].…”
Section: Molecular Mechanisms Involved In Cscs Radioresistancementioning
confidence: 99%
“…Cancer stem cells (CSCs) are considered to contribute to radioresistance of tumors [5] due to several genetic and cellular adaptations, such as efficient DNA repair, hypoxia microenvironment and cell cycle blocked in the G0/G1-phase [6]. The expression of core pluripotency stem cell genes, including Homeobox Transcription Factor Nanog (NANOG), octamer-binding transcription factor 4 (OCT4) and sex determining region Y-box 2 (SOX2), play an important role in regulating selfrenewal and multi-lineage differentiation of cancer stem cells.…”
Section: Introductionmentioning
confidence: 99%